The long ago : a novel - McGarrity, Michael (W.W. Norton & Company, 2023)
Returning home from Vietnam when his sister goes missing, soldier Ray Landsdale embarks on a relentless search that takes him from Montana to Hollywood to L.A. and beyond, forcing him to confront his worst nightmare.